Using laboratory experiment to inform local adaptation policies for extreme heat events. Issue 136 (October 2022) - Yang, Jianxun; Gao, Qi; Liu, Miaomiao; Wang, Qingqing; Ding, Zhen; Liu, Mao; Bi, Jun
Abstract: Issuing early heat warnings and enhancing public climate change awareness and engagement are important local policy options for heat wave adaptation. Here, we used a laboratory experiment to inform major gaps in making these two policies, including setting proper thresholds for heat alerting systems and figuring out how heat experience shifts individuals' climate change perceptions. Taking Nanjing as a case city, we simulated a heat event by increasing temperature from 25 °C to 40 °C (70% relative humidity) in a climate chamber and recruited 58 young adults as participants. Physical thermal responses, including skin temperature and heart rate variability, were recorded using portable devices. Subjective thermal perceptions, climate change belief and psychological distance were measured by self-rated scales before, during, and after the exposure. We found physiological responses were correlated with subjective thermal perceptions and showed sharp rises from 30° to 35°C, presenting aggravated thermal discomfort. Moreover, heat exposure increased climate change belief and reduced psychological distance significantly. After the experiment, follow-up surveys showed participants had a short memory of the heat exposure, but daily temperature variations still predicted climate change belief. The findings suggest in our case city, the current threshold (35 °C) for heat warnings may not be safe enough. Local authorities should consider prolonged periods of hot weather with temperature between 30 and 35 °C. Due to strong links between heat experience and climate change perceptions, we encourage to take this "window of opportunity" when heat events occur to communicate climate risks and enact post-event policy changes. Graphical Abstract: ga1 Highlights: We exposed 58 subjects in Nanjing to a simulated heat event in a climate chamber. Psycho-physiological responses were correlated and showed sharp rises from 30° to 35°C. Heat exposure increased climate change belief and reduced psychological distance. Policy implications are given for heat warning thresholds and climate risk communications.